Comparison between Trigonometric, and traditional DDS, in 90 nm technology - Cardarilli Gian Carlo; Di Nunzio Luca; Fazzolari Rocco; Giardino Daniele; Matta Marco; Nannarelli Alberto; Re Marco; Silvestri Francesca; Spanò Sergio (Universitas Ahmad Dahlan, 2018)
The Direct Digital frequency Synthesizer (DDS) is an architecture largely used for the generation of numeric sine and/or cosine waveforms in different applications. In this work, authors compare two different DDS architectures: the traditional architecture, based on the exploitation of quarter wave symmetry, and the Symon’s DDS (trigonometric DDS) presented in 2002. The two layout configurations have been implemented in 90 nm technology and compared in terms of area, speed and power consumption. Comparisons have been performed in terms of circuital complexity on architectures having the same Spurious Free Dynamic Range (SFDR) and phase resolution. Experiments show that the trigonometric architecture is very efficient in terms of area.